Planning accessibility strategies and connectivity for Malaysian urban built environment - Abd Samad, Nur Amirah; Said, Ismail; Abdul Rahim, Asiah (IOS Press, 2018)
Access to our buildings relies to the accessibility of its external environment and the route taken. Developments and planning in urban areas has many several requirements and restrictions. Planning accessibility for Malaysian built environment is achievable by designing in compliance to the requirements enforced by authorities. Accessible design is commonly associated with providing facilities for Persons with Disabilities (PwDs), the issue that is often brought up is the inaccessibility of the external environment and lacking of seamless connectivity between buildings and the outdoor. The intention is to formulate accessibility strategies and work out planning process on how accessibility can be achieved. Universal Design will be the basis for the design and planning concept to accommodate all users to enjoy our urban built environment. It is notable that developed countries advances more in terms of implementing and enforcing accessibility measures via legislative and regulatory documents, government strategies and initiatives within its planning approach than the developing nations. The methodology will be looking into the establishment of strategies and measures of international and local planning policy, local and action plans of City of London as selected Local Authority to be analyzed its inclusive policy has been successfully implemented in their jurisdiction. The findings, discussions and result will be an outcome of generating a framework of accessibility strategies that is derived from interviews and government documents accordingly to targeted Malaysian urban areas focusing the City of Petaling Jaya and Putrajaya and how it can be improvised. Therefore, an interpretation of adopting accessibility planning strategies of developed country, to be adapted locally according to Malaysian legislation, culture and lifestyles.